Las competencias en innovación de los estudiantes de grado de la Universidad Técnica de Cotopaxi: caso Ideatón UTC 2022. - Velasco Panchi, Oscar Bladimir (2023)
Innovation in college can foster creativity and critical thinking in students by challenging them to find innovative solutions to problems they face in their academic environment. By providing opportunities for experimentation and hands-on learning, innovation can help students develop valuable skills they can apply in their future careers. With this background, the objective of this research was to know the level of innovation of the students participating in the integrative activity called “Ideatón UTC 2022” carried out by the master's program in Business Administration cohort 2022-1, the methodology applied was with a Descriptive quantitative approach, with a study population of 115 students from different majors at the Technical University of Cotopaxi, the INCODE-ICB v5 instrument was applied; The distribution of the population by career was as follows: 19.1% Accounting and Auditing, 7% Information Systems, 30.4% Business Administration, 13.9% Electromechanics, 20% Graphic Design, 7.8% Engineering Electrical and 1.7 Commercial, , giving a high symmetry, that is, its correlation is positive and its results will therefore be positive towards innovation.